Sensex a true reflector of economic growth – myth or reality: a case of India - RASTOGI, DR HIMANSHU; KESERWANI, DR HITESH (The journal of contemporary issues in business and government, 2021)
Stock exchange indices are often considered as a reflector of nation’s economic wellbeing, but the point is that how closely are the two associated to one and another and does growing Sensex actually guarantees rapid growth of economy, is something needs to be analyzed. The present paper is aimed to find if any relationship exists amid economic growth and Sensex and also to see whether Sensex is reflective of national growth or other factors are more instrumental to set the direction of Sensex even though the economy is not performing as per the expectations. For this purpose, a retrospective study was carried out. BSE Sensex growth rates for the last 10 years have been taken into consideration and corelated with Gross Domestic Product (GDP). Statistically there was no significant correlation established between Sensex and Economic Growth. Most of the times it has been found that even though the Sensex is zooming still the economic growth is lagging the reason been that Sensex is guided more by the performance of select companies which form the Sensex basket while the performance of economy is a result of many more factors which gives direction to economy rather than the Sensex alone. The paper tries to highlight the various factors which gives direction to economic growth than the Sensex itself alone. The paper is based on secondary source of information derived from reliable websites, research papers, government sites etc.